PERANAN REMEDIAL TEACHING DALAM MENINGKATKAN KEMAMPUAN MEMBACA PADA ANAK DENGAN MILD INTELLECTUAL DISABILITY - Shanty Sudarji (Psibernetika, 2011)
The goal of this research is to see the role of remedial teaching in increasing reading capability on children with mild intellectual disability. According to Diagnostic and Statistical Manual of Mental Disorders (DSM-IV-TR), intellectual disability is individuals with intellectual functions significantly below average, with IQ score about 70 or lower, suffering disorders in adaptive functions in at least two areas, with onset surfacing before 18 years of age. Academically, children with intellectual disability generally suffer delays in reading, writing, and simple arithmetic. Remedial teaching can be used as one of the method to increase reading capability on children with mild intellectual disability. There are two subjects in this research, male and female. Data is collected from observations, interviews, and psychological examination. The result of this research suggests that remedial teaching is able to increase reading capability of children with mild intellectual disability. There is an increase of 27 syllables in reading capability on the first subject, while the second subject have an increase of 24 syllables, comparing between pre-test and post-test data. Keywords: children with mild intellectual disability, reading capability,remedial teaching.